Why Calories Count : From Science to Politics - Nestle, Marion; Nesheim, Malden C. (California studies in food and culture, 2012)
Calories--too few or too many--are the source of health problems affecting billions of people in today's globalized world. Although calories are essential to human health and survival, they cannot be seen, smelled, or tasted. They are also hard to understand. In Why Calories Count, Marion Nestle and Malden Nesheim explain in clear and accessible language what calories are and how they work, both biologically and politically. As they take readers through the issues that are fundamental to our understanding of diet and food, weight gain, loss, and obesity, Nestle and Nesheim sort through a great d.